Computational modelling of amino acid exchange and facilitated transport in placental membrane vesicles. (21st January 2015) - Panitchob, N.; Widdows, K.L.; Crocker, I.P.; Hanson, M.A.; Johnstone, E.D.; Please, C.P.; Sibley, C.P.; Glazier, J.D.; Lewis, R.M.; Sengers, B.G.
Abstract: Placental amino acid transport is required for fetal development and impaired transport has been associated with poor fetal growth. It is well known that placental amino acid transport is mediated by a broad array of specific membrane transporters with overlapping substrate specificity. However, it is not fully understood how these transporters function, both individually and as an integrated system. We propose that mathematical modelling could help in further elucidating the underlying mechanisms of how these transporters mediate placental amino acid transport. The aim of this work is to model the sodium independent transport of serine, which has been assumed to follow an obligatory exchange mechanism. However, previous amino acid uptake experiments in human placental microvillous plasma membrane vesicles have persistently produced results that are seemingly incompatible with such a mechanism; i.e. transport has been observed under zero-trans conditions, in the absence of internal substrates inside the vesicles to drive exchange. This observation raises two alternative hypotheses; (i) either exchange is not fully obligatory, or (ii) exchange is indeed obligatory, but an unforeseen initial concentration of amino acid substrate is present within the vesicle which could drive exchange. To investigate these possibilities, a mathematical model for tracer uptake was developed based on carrier mediated transport, which can represent either facilitated diffusion or obligatory exchange (also referred to as uniport and antiport mechanisms, respectively). In vitro measurements of serine uptake by placental microvillous membrane vesicles were carried out and the model applied to interpret the results based on the measured apparent Michaelis–Menten parameters K m and V max . In addition, based on model predictions, a new time series experiment was implemented to distinguish the hypothesised transporter mechanisms. Analysis of the results indicated the presence of a facilitated transport component, while based on the model no evidence for substantial levels of endogenous amino acids within the vesicle was found. Highlights: Initial rate and time course data for serine uptake in placental membrane vesicles. Integrated model analysisof facilitative diffusion vs obligatory exchange. Dependency apparent Michaelis–Menten constants on internal concentrations. Uptake in placental vesicles was consistent with a facilitative transport component. No effects of any internal endogenous substrate in vesicles were apparent.